Women Empowerment through Emily Brontë’s Wuthering Heights - Perdones Cañas, Rebeca (Journal of Artistic Creation and Literary Research, 2025)
In this paper I analyse how Emily Brontë challenges in her novel Wuthering Heights the female stereotypes to which women of the Victorian Era were submitted. In order to accomplish this analysis, I take into account the social aspects in which women had to meet expectations. For the purpose of finding answers to this issue, I have organised this study into different parts that show the pressure to which women of the Victorian age were subjected. Firstly, I start analysing the age in which this novel takes place and how the situation of women in that time was. Secondly, I continue describing one of the most important social aspects that kept women submitted in that age: marriage. I analyse the clout that it had in Victorian society and how it was a social imposition and nobody had a different choice. Thirdly, I focus on women education and how it was something almost forbidden for them and a way to control and submit them. Fourthly, my study comes to the most important issue which is the female stereotypes challenged by the characters of Wuthering Heights. Then, I explore superficially how the defiance of these stereotypes lead to tragic consequences in the case of the main female characters. Finally, I conclude that Emily defies the imposed gender roles and female stereotypes of the Victorian Era through her work although it was not a simple task.